Model Implementasi Kebijakan Ketahanan Pangan Berbasis Dana Desa - Alexsander Alexsander; Alamsyah Alamsyah; Hernowo Noviyanto; Rahiman Dani (Jurnal STIA Bengkulu, 2026)
This study aims to analyze the implementation model of village fund-based food security policy in several villages in Batik Nau Subdistrict, North Bengkulu Regency. Food security is a strategic issue influenced by structural, environmental, and local institutional capacity factors. Although Village Funds have been directed to support food security programs, their implementation at the village level still faces various challenges, such as limited human resources, low institutional capacity, and suboptimal coordination among stakeholders.This research employs a qualitative approach with a case study design. Data were collected through interviews, observations, and documentation involving key actors such as village governments, farmer groups, and the community. The analysis was conducted using the Miles and Huberman interactive model and the Contextual Interaction Theory (CIT) approach to understand the interaction between policy, actors, and local context.The results indicate that the implementation of food security programs has been carried out through participatory mechanisms and has produced outputs in the form of agricultural, livestock, and fishery activities. However, the outcomes are still limited to meeting household food needs and have not significantly improved community welfare. Supporting factors include community participation and local potential, while inhibiting factors include limited human resource capacity, weak institutional structures, and lack of assistance and program integration.This study concludes that an effective policy implementation model requires strengthening village institutional capacity, enhancing inclusive community participation, and adapting policies based on local context.